Realization of the mechanism of control software integrity in post quantum period - Potii, O.V.; Karpenko, А.S. (Radiotekhnika, 2018)
This article is devoted to description the realization of the public-key infrastructure using the stateless algorithm of digital signature with quantum-resistance. This article is detail describe the development cycle and implementation of the stateless signature scheme using the hash function of  DSTU 7564:2014.